Penerapan Teknologi Digital dalam Pembelajaran Bahasa Indonesia di Universitas Muhammadyah Maumere - Elisabeth Gustina Nesti; Trisnawati Bura; Katharina Woli Namang (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to analyze the application of digital technology in Indonesian language learning at the Muhammadiyah University of Maumere. Digital technology has changed the way of learning in higher education, especially in overcoming educational challenges in the digital era. Through interviews, observations and documentation studies, this research identifies the advantages, challenges and impacts of digital technology in Indonesian language learning. The research results show that although digital technology increases accessibility and interactivity, limited infrastructure and digital skills are still major obstacles. Therefore, this research provides recommendations for strengthening infrastructure and technology training for lecturers and students.